Advances, challenges and future applications of liver organoids in experimental regenerative medicine - Gong, Da; Mo, Jiaye; Zhai, Mei; Zhou, Fulin; Wang, Guocai; Ma, Shaohua; Dai, Xiaoyong; Deng, Xuesong (Frontiers in Medicine, 2025)
The liver is a vital organ responsible for numerous metabolic processes in the human body, including the metabolism of drugs and nutrients. After liver damage, the organ can rapidly return to its original size if the causative factor is promptly eliminated. However, when the harmful stimulus persists, the liver’s regenerative capacity becomes compromised. Substantial theoretical feasibility has been demonstrated at the levels of gene expression, molecular interactions, and intercellular dynamics, complemented by numerous successful animal studies. However, a robust model and carrier that closely resemble human physiology are still lacking for translating these theories into practice. The potential for liver regeneration has been a central focus of ongoing research. Over the past decade, the advent of organoid technology has provided improved models and materials for advancing research efforts. Liver organoid technology represents a novel in vitro culture system. After several years of refinement, human liver organoids can now accurately replicate the liver’s morphological structure, nutrient and drug metabolism, gene expression, and secretory functions, providing a robust model for liver disease research. Regenerative medicine aims to replicate human organ or tissue functions to repair or replace damaged tissues, restore their structure or function, or stimulate the regeneration of tissues or organs within the body. Liver organoids possess the same structure and function as liver tissue, offering the potential to serve as a viable replacement for the liver, aligning with the goals of regenerative medicine. This review examines the role of liver organoids in regenerative medicine.